2019
DOI: 10.1002/app.47861
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of acoustic performances of a new tung oleic acid‐based composite polyurethane foam

Abstract: Bio‐based polyurethane (PU) foam, different from traditional PU foam, is a new green environmental acoustic material. It can be used in the field of automobiles. In this work, a new tung oleic acid‐based composite PU (TOAPU) foam was prepared using tung oleic acid‐based polyol and polyether polyols 3630. It is important to optimize the formulation of TOAPU foam for better acoustic performance. The effect of each component on the acoustic performance of TOAPU is ordered by screening test. A1, silicone, and A33,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…As a result, green PU foams with satisfactory mechanical and thermal properties were produced. Bio‐based PU foams were successfully fabricated from tung oleic acid‐based polyol by Ji and Chen 30 . The oleic acid‐based composite PU foams displayed good acoustic properties with satisfactory sound absorption coefficient and transmission loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, green PU foams with satisfactory mechanical and thermal properties were produced. Bio‐based PU foams were successfully fabricated from tung oleic acid‐based polyol by Ji and Chen 30 . The oleic acid‐based composite PU foams displayed good acoustic properties with satisfactory sound absorption coefficient and transmission loss.…”
Section: Resultsmentioning
confidence: 99%
“…Bio-based PU foams were successfully fabricated from tung oleic acidbased polyol by Ji and Chen. 30 The oleic acid-based composite PU foams displayed good acoustic properties with satisfactory sound absorption coefficient and transmission loss. Polyols derived from oleic acid, on the other hand, are a good candidate for production of coatings.…”
Section: Prospective Application Of Urethane From Uoa As An Eco-frien...mentioning
confidence: 95%
“…Using Tung oleic acid-base polyol and polyether polyols a new biobased PU foam different from common PU foam was prepared. The study found that the biobased PU mean sound absorption coefficient and transmission loss can reach 0.515 and 21.389 dB [91].…”
Section: Acousticsmentioning
confidence: 95%
“…The resulting products could be applied as building construction and electromagnetic shielding materials . Many studies on the compression performance of PU foam have been conducted . Yan et al combined a inter/intraply hybrid laminate on high‐density flexible PU foam to improve its mechanical properties .…”
Section: Introductionmentioning
confidence: 99%